Analyze of Fifth Highest Hunger Index in Asean: Does Fraud, Food Policy, and Income Matter? - Yogandhi , Ni Putu Sintha Devi (JURNAL MANAJEMEN MOTIVASI, 2026)
Hunger and food insecurity remain key challenges in Southeast Asia. This study analyzes the determinants of the hunger index in Timor Leste, Laos, Indonesia, Myanmar, and Cambodia using panel data from 2011–2019 and dynamic panel estimation via the Generalized Method of Moments. Key variables include past hunger levels, corruption, food security, social protection, poverty, and human capital. Results show strong persistence of hunger and significant effects of all examined variables. The findings underscore the need for integrated policies to improve governance, food systems, social protection, and human capital to effectively combat hunger in the region.